Decentralization, local government elections and voter turnout in Pakistan - Akramov, Kamiljon T.; Qureshi, Sarfraz; Birner, Regina; Khan, Bilal Hasan (International Food Policy Research Institute, 2008)
Decentralization has the potential to improve the accountability of government and lead to a more efficient provision of public services. However, accountability requires broad groups of people to participate in local government. Thus, voter turnout at local government elections is an important component of government accountability. This study used survey data on the 2005 local government elections in Pakistan to analyze the impact of electoral mechanisms, the credibility of elections, and voters? socioeconomic characteristics on voter turnout. The rational-choice perspective is applied to develop the specifications of the empirical model. The empirical analysis is based on a series of standard and multilevel random-intercept logistic models. Our important findings reveal that (1) voter turnout is strongly associated with the personal and social gratifications people derive from voting; (2) the preference-matching ability of candidates for local government positions is marginal; and (3) the introduction of direct elections of the district nazims?a key position in local government?might improve electoral participation and thus create a precondition for better local government accountability. The findings also suggest that less educated people, farmers, and rural people are more likely to vote.